Long-Lasting Sex-Specific Effects Based On Emotion- and Cognition-Related Behavioral Assessment of Adult Rats After Post-Traumatic Stress Disorder From Different Lengths of Maternal Separation - Yang, Rucui; Sun, Haoran; Wu, Yani; Lu, Guohua; Wang, Yanyu; Li, Qi; Zhou, Jin; Sun, Hongwei; Sun, Lin (Frontiers in Psychiatry, 2019)
Adverse early life stress is a major cause of vulnerability to various mental disorders in adulthood, including post-traumatic stress disorder (PTSD). Recent studies have suggested that early life stress can help the body adapt optimally when faced with stressful trauma in adult life. An interaction may exist between early life stress (e.g., childhood trauma) and vulnerability to PTSD. This study aimed to evaluate emotion-related behaviors and verify the long-lasting effects of cognitive aspects of PTSD after exposure to severe adverse early life stress, such as long-term separation. Adverse early life stress was simulated by subjecting rats to 3 or 6 consecutive hours of maternal separation (MS) daily, from postnatal day (PND) 2 to PND 14. Single-prolonged stress (SPS) was simulated on PND 80 to imitate other adulthood stresses of PTSD with gender divisions (M-MS3h-PTSD, F-MS3h-PTSD, M-MS6h-PTSD, F-MS6h-PTSD, M-PTSD, and F-PTSD). After the MS and PTSD sessions, behavioral tests were conducted to assess the effectiveness of these treatments, which included an elevated open field test (OFT), plus maze test (EPMT), water maze test (WMT), and forced swimming test (FST) to detect anxiety-like behavior (OFT and EPMT), memory behavior (WMT), and depressive behavior (FST). The M-MS3h-PTSD group had fewer time entries into the open arms of EPMT than the F-MS3h-PTSD group, and the M-MS6h-PTSD group demonstrated fewer up-right postures in the OFT than the F-MS6h-PTSD group. The M-MS3h-PTSD group exhibited more exploratory behavior than the M-MS6h-PTSD and M-PTSD groups in the OFT. Less exploratory behavior was observed in the F-MS3h-PTSD group than in the F-MS6h-PTSD group, which demonstrated significantly increased freezing times in the FST compared to the F-PTSD group. The WMT revealed significant differences in learning and memory performance between the M-MS3h-PTSD group and other treatment groups, which were not found in the female rats. These findings demonstrate that an early stressful experience, such as MS, may be involved in helping the body adapt optimally when faced with additional trauma in adulthood, although mild early life stress might benefit learning and memory among males.